A novel compact tree-design antenna (NCTA) with high gain enhancement for UWB application - M. T., Jusoh; Mohd Faizal, Jamlos, Dr.; Muhammad Ramlee, Kamarudin; Mohd Fareq, Abd. Malek; Mahathir, H. Mat (Taylor & Francis Group, 2012)
Link to publisher's homepage http://www.tandfonline.com/